Bubble formation and interface phenomena of aqueous solution under microwave irradiation - Asakuma, Y.; Nakata, R.; Asada, M.; Kanazawa, Y.; Phan, Chi (Elsevier Ltd, 2016)
© 2016 Elsevier LtdWater behavior during and after microwave irradiation is important phenomena for industrial applications. Recently, we reported a non-thermal effect of microwave on water surface tension. The bubble formation during microwave irradiation was suggested as one of the underpinning causes. This study examined the possibility by monitoring bubble formation during and after microwave irradiation. Moreover, the influence of NaCl on surface tension and bubble formation were also investigated. It was found that the presence of NaCl strongly increased both bubble formation and surface tension effect. The results indicated that bubble formation played an important role in surface tension reduction. The phenomena can provide useful pathways to improve the efficiency of chemical processes with microwave.